h - Gilbert, Henri; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the 29th Annual International Conference on the Theory and Applications of Cryptographic Techniques, EUROCRYPT 2010, held on the French Riviera, in May/June 2010. The 33 revised full papers presented together with 1 invited lecture were carefully reviewed and selected from 188 submissions. The papers address all current foundational, theoretical and research aspects of cryptology, cryptography, and cryptanalysis as well as advanced applications. The papers are organized in topical sections on cryptosystems; obfuscation and side channel security; 2-party protocols; cryptanalysis; automated tools and formal methods; models and proofs; multiparty protocols; hash and MAC; and foundational primitives.
Cryptosystems I -- On Ideal Lattices and Learning with Errors over Rings -- Fully Homomorphic Encryption over the Integers -- Converting Pairing-Based Cryptosystems from Composite-Order Groups to Prime-Order Groups -- Fully Secure Functional Encryption: Attribute-Based Encryption and (Hierarchical) Inner Product Encryption -- Obfuscation and Side Channel Security -- Secure Obfuscation for Encrypted Signatures -- Public-Key Encryption in the Bounded-Retrieval Model -- Protecting Circuits from Leakage: the Computationally-Bounded and Noisy Cases -- 2-Party Protocols -- Partial Fairness in Secure Two-Party Computation -- Secure Message Transmission with Small Public Discussion -- On the Impossibility of Three-Move Blind Signature Schemes -- Efficient Device-Independent Quantum Key Distribution -- Cryptanalysis -- New Generic Algorithms for Hard Knapsacks -- Lattice Enumeration Using Extreme Pruning -- Algebraic Cryptanalysis of McEliece Variants with Compact Keys -- Key Recovery Attacks of Practical Complexity on AES-256 Variants with up to 10 Rounds -- IACR Distinguished Lecture -- Cryptography between Wonderland and Underland -- Automated Tools and Formal Methods -- Automatic Search for Related-Key Differential Characteristics in Byte-Oriented Block Ciphers: Application to AES, Camellia, Khazad and Others -- Plaintext-Dependent Decryption: A Formal Security Treatment of SSH-CTR -- Computational Soundness, Co-induction, and Encryption Cycles -- Models and Proofs -- Encryption Schemes Secure against Chosen-Ciphertext Selective Opening Attacks -- Cryptographic Agility and Its Relation to Circular Encryption -- Bounded Key-Dependent Message Security -- Multiparty Protocols -- Perfectly Secure Multiparty Computation and the Computational Overhead of Cryptography -- Adaptively Secure Broadcast -- Universally Composable Quantum Multi-party Computation -- Cryptosystems II -- A Simple BGN-Type Cryptosystem from LWE -- Bonsai Trees, or How to Delegate a Lattice Basis -- Efficient Lattice (H)IBE in the Standard Model -- Hash and MAC -- Multi-property-preserving Domain Extension Using Polynomial-Based Modes of Operation -- Stam$1 (Bs Collision Resistance Conjecture -- Universal One-Way Hash Functions via Inaccessible Entropy -- Foundational Primitives -- Constant-Round Non-malleable Commitments from Sub-exponential One-Way Functions -- Constructing Verifiable Random Functions with Large Input Spaces -- Adaptive Trapdoor Functions and Chosen-Ciphertext Security.s
Keywords: Computer science; Computer Communication Networks; Data protection; Data encryption (Computer science).; Computer software; Computational complexity; Information Systems; Computer Science; Data Encryption; Systems and Data Security; Computer Communication Networks; Management of Computing and Information Systems; Algorithm Analysis and Problem Complexity; Discrete Mathematics in Computer Science